Research of the overall chemical and amino acid composition of meat from young animals of new sheep genotypes - O. N. Orlova; V. S. Mkrtichyan; L. V. Skrypnik; L. V. Krichun (Теория и практика переработки мяса)
The paper presents the results of the investigation of the overall chemical composition (mass fraction of moisture, fat, protein and ash) and the amino acid composition of mutton from the experimental animals of new genotypes: Sovetsky Merino x Dzhalginsky Merino and Sovetsky Merino x Stavropolsky breed. As a control, meat of purebred Sovetsky Merino was studied. The experimental and control rams were slaughtered at the age of 8 months by the conventional technology. Meat samples for laboratory examination were taken a day after slaughter. The results of the analysis of the overall chemical composition showed that lamb meat of new genotypes had lower moisture content and higher content of fat and protein compared to the control. Analysis of the amino acid composition of meat proteins of genotypes Sovetsky Merino x Dzhalginsky Merino and Sovetsky Merino x Stavropolsky breed revealed lower content of essential amino acids compared to the control. Comparison of amino acid scores showed that the amino acid composition of meat proteins from the experimental animals was limited by valine and lysine, respectively. It was concluded by the results of the investigations of the amino acid composition of proteins that the biological full value of proteins of mutton from new genotypes was 22.9% and 30.3% lower than that of the control.